2020
DOI: 10.1136/bmjopen-2019-031203
|View full text |Cite
|
Sign up to set email alerts
|

Differences in reimbursement listing of anticancer therapies in China: an observational study

Abstract: ObjectiveAccess to highly priced anticancer medications usually requires insurance coverage. A first step towards coverage of such medications is their inclusion in reimbursement lists. We assessed listing for reimbursement in China between 2009 and 2018 of anticancer medications on the WHO’s Essential Medicines List.Setting and study designUsing publicly available data, we assessed which anticancer medications listed in the 20th WHO Model List of Essential Medicines (EML) were included in China’s National Rei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 16 publications
0
17
0
Order By: Relevance
“…Prior to 2017, most insured patients needed to pay for expensive targeted anticancer medications entirely out-of-pocket (OOP) except in few provinces or cities which had included the medications in their reimbursement lists. 5 To improve patient and system affordability and decrease health inequity, the Chinese government implemented a series of policies, including reimbursement-linked central medication price negotiations. 7 We found that after national medication price negotiations in 2017, procurement volumes of all pricenegotiated anticancer medications increased abruptly and significantly, except for bortezomib for which use increased initially and declined in 2018.…”
Section: Principal Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior to 2017, most insured patients needed to pay for expensive targeted anticancer medications entirely out-of-pocket (OOP) except in few provinces or cities which had included the medications in their reimbursement lists. 5 To improve patient and system affordability and decrease health inequity, the Chinese government implemented a series of policies, including reimbursement-linked central medication price negotiations. 7 We found that after national medication price negotiations in 2017, procurement volumes of all pricenegotiated anticancer medications increased abruptly and significantly, except for bortezomib for which use increased initially and declined in 2018.…”
Section: Principal Findingsmentioning
confidence: 99%
“…4 To promote access to healthcare, including access to cancer care and anticancer medications, China has since 2009 implemented a series of linked policies (see box 1). As medications listed in the national reimbursement list must be paid at least in part by China's health insurance system, 5 including new medications in the National Reimbursement Drug List (NRDL) is the main approach for…”
Section: Introductionmentioning
confidence: 99%
“…Since 2015, the number of annual publications and the total number of publications in China have exceeded those of Germany, becoming the country with the second most publications. In the field of cancer research, the number of publications in China has increased significantly in recent years ( 23 , 24 ), probably because cancer has become a major cause of death in China since 2010, and China has increased its investment in scientific research on public health and other fields in recent years ( 25 ). Notably, the total citations and the average number of citations of papers published by Chinese scholars were relatively low, and none of the 10 most cited papers were published by Chinese scholars, indicating that the quality of papers published by Chinese researchers needs to be further improved.…”
Section: Discussionmentioning
confidence: 99%
“…Since 2014, the number of annual publications and the total number of publications in China exceeded those of Germany, becoming the country with the second most publications. In the eld of cancer research, the number of publications in China has increased signi cantly in recent years [14], probably because cancer has become a major cause of death in China since 2010 [15], and China has increased its investment in scienti c research on public health and other elds in recent years [16]. However, it is worth noting that the total citations and the average number of citations of papers published by Chinese scholars are relatively low, and there is no paper published by Chinese scholars among the 10 most cited papers, indicating that the quality of these papers needs to be further improved.…”
Section: Discussionmentioning
confidence: 99%